2017
DOI: 10.1371/journal.pone.0187275
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support and health-related quality of life among Chinese seafarers: A cross-sectional study

Abstract: BackgroundSeafarers have reported impaired health and health-related quality of life (HRQOL). Social support might increase HRQOL, but little is known about this association among Chinese seafarers. The aim of this study was to describe social support and explore its association with HRQOL among Chinese seafarers.MethodsA cross-sectional survey was conducted in the ports of Nantong and Rugao, China, from April to December 2013. A total of 917 Chinese seafarers were interviewed on social support, mental distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 42 publications
4
44
0
2
Order By: Relevance
“…Not surprisingly, this study indicated that both formal and informal social support could generally improve HRQOL for the elderly, generally confirming the findings of previous studies [6][7][8][9][10][11]15]. The social support provided by families, communities and governments together forms the social support system of the Chinese rural elderly.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Not surprisingly, this study indicated that both formal and informal social support could generally improve HRQOL for the elderly, generally confirming the findings of previous studies [6][7][8][9][10][11]15]. The social support provided by families, communities and governments together forms the social support system of the Chinese rural elderly.…”
Section: Discussionsupporting
confidence: 89%
“…[6][7][8]. In recent years, an increasing number of studies have been conducted to explore the relationship between social support and HRQOL, demonstrating that higher social support could effectively relieve the pressure on individuals and increase their subjective wellbeing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Müller et al (2016) likewise found that the QoL of Brazilian fishermen were lower than that of the general population, with physical health being the most impaired area. In a study of Chinese seafarers, Xiao et al (2017) found that environmental domain scores were significantly lower than other QoL domain scores, consistent with our supposition that the particular characteristics of the fisherman occupation explain, at least in part, the lower QoL of fishermen compared to the general population. FIGURE 1 | SEM direct effect path diagram.…”
Section: Discussionsupporting
confidence: 87%
“…The SSRS was originally developed by Cauce et al (1982) with the intention to examine individual support received in society across three subscales: family support, formal support, and informal support ( Stromborg and OIsen, 2004 ). The Chinese version of SSRS was revised by Xiao (1994 , 1999) with the similarity of three dimensions, subjective support, objective support, and support utilization, and has been commonly used as a measure assessing SS in China ( Xiao et al, 2017 ). The total support score is the sum from the three subscales.…”
Section: Methodsmentioning
confidence: 99%